2019
DOI: 10.1111/jse.12482
|View full text |Cite
|
Sign up to set email alerts
|

Plastome phylogenomic analysis of Torreya (Taxaceae)

Abstract: Torreya Arn., a small genus of Taxaceae, consists of six species occurring in North America and eastern Asia. Several phylogenetic studies have previously been undertaken to reveal relationships within this genus, although only a few DNA segments or species were used. In the present study, we sequenced five Torreya plastomes and combined these with two existing plastomes from the genus to investigate plastome evolution and phylogenetic relationships within Torreya. All sequenced Torreya plastomes shared the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 51 publications
6
50
3
Order By: Relevance
“…All plastomes of Thuja possess 116 unique genes arranged in the same order, including 82 protein coding genes, 30 tRNA genes, and 4 rRNA genes, with trnI-CAU and trnQ-UUG having two copies. Previous studies have commonly reported that the plastomes of conifers are usually characterized by the loss of an IR [36][37][38][39][40][41][42][43][44], which is different from the typical quadripartite structure shared by most angiosperm plastomes [45]. As expected, the loss of an IR was evident in all Thuja plastomes.…”
Section: Characterizations Of Thuja Plastomessupporting
confidence: 56%
See 2 more Smart Citations
“…All plastomes of Thuja possess 116 unique genes arranged in the same order, including 82 protein coding genes, 30 tRNA genes, and 4 rRNA genes, with trnI-CAU and trnQ-UUG having two copies. Previous studies have commonly reported that the plastomes of conifers are usually characterized by the loss of an IR [36][37][38][39][40][41][42][43][44], which is different from the typical quadripartite structure shared by most angiosperm plastomes [45]. As expected, the loss of an IR was evident in all Thuja plastomes.…”
Section: Characterizations Of Thuja Plastomessupporting
confidence: 56%
“…Consistent with previous studies, we detected two repeated tRNA genes, trnI-CAU and trnQ-UUG, existing inall Thuja plastomes. As proposed previously [37,41,44], these types of repeated tRNA genes in direct or inverted copies are possibly the result of the incomplete loss of IR regions.…”
Section: Characterizations Of Thuja Plastomesmentioning
confidence: 55%
See 1 more Smart Citation
“…Dealing with the rearrangements of two specific inverted fragments, our study provides novel insights into the structural diversification of Taxaceae plastomes. Phylogeny of the Taxaceae genera has been controversial for many years (Lu et al, 2014;Wu and Chaw, 2016;Zhang et al, 2019). In this study, 73 shared protein-coding genes were used to determine the relationships among the four genera.…”
Section: Discussionmentioning
confidence: 99%
“…The tribe Maleae of Rosaceae had an early New World diversification and subsequently diversified in Asia. Zhang et al () conduct plastome phylogenomic analyses of Torreya and infer the divergence between the eastern North American T. taxifolia with its eastern Asian relatives in the late Miocene, but a much younger disjunction is inferred between the western North American T. californica and the eastern Asian T. grandis . The authors argue for the climatic oscillations and environmental changes during and after the late Tertiary in shaping up the intercontinental biogeography of Torreya .…”
mentioning
confidence: 99%